The rise and fall of language diversity through the Holocene - D. E. Blasi; M. J. Hamilton; R. D. Gray; C. L. Bowern (Science, 2026)
Characterizing the factors that have shaped linguistic diversity is fundamental for understanding human history, culture, and cognition. In this study, we combined statistical and social computational modeling, ethnographic data, and paleodemographic inference to model trajectories of global linguistic diversity. Before the onset of plant and animal domestication, the number of languages was smaller than it is today (4500 to 6000 compared with 7500). Subsequent increases in global population precipitated increased linguistic diversity. We uncovered a linguistic “golden age” with tens of thousands of languages 3000 to 1000 years ago. Great loss of linguistic diversity did not begin with recent colonial expansion but as multinational empires first spread along with their languages, pathogens, and cultures. Thus, extinction has likely played a much greater role in shaping linguistic and cultural diversity than previously thought.